Differential effects of the ethanol acute or chronic exposure on the early hypoxic ventilatory response (hvr) in rat neonates - Macchione, Ana Fabiola (2021)
Early ethanol exposure disrupts neonatal respiratory patterns and it has been suggested as risk factor associated with the Sudden Infant Death Syndrome. Ambient hypoxia acts as an environmental stressor eliciting breathing adaptations that may be altered by the EtOH exposure. However, the specific effects induce by chronic, acute or the combination of them EtOH intoxication are not clearly understood. In an animal model equivalent to the 3rd human gestational trimester, breathing frequencies and apneas were recorded against an intermittent hypoxic experience as a function of EtOH pre-exposure and/or acute EtOH intoxication. Pups pre-exposed to 0.0 or 2.0g/kg of EtOH (DPs 3-5-7, ig) were evaluated at DP9 in sobriety-0.0g/kg- or under the state of EtOH intoxication-2.0g/kg-. Breathing rates and apneas were recorded through whole body plexismography during 35 minutes [5 min of initial normoxia, followed by 3 episodes of hypoxia (O2 8%) of 5 min, separated by periods of recovery-normoxia of the same duration].First acute EtOH intoxication diminished the hypoxic ventilatory response (HVR) during the test (p=0.034) relative to it expressed in pups never intoxicated. The prior experience with the drug significantly modified the HVR patterns, as follow: in sobriety, EtOH pre-exposed pups exhibited a depressed HVR relative to vehicle pre-exposed pups. On the contrary, under the state of intoxication, EtOH pre-exposed pups elicited an exacerbated HVR when were defied by hypoxia respect to vehicle pre-exposed pups. With regard to apneas, an increase in the number of apneas was triggered by both, the first acute EtOH intoxication or by the history with the drug in sober pups (p= 0.017). In summary, specific HVR alterations and apneic episodes occurrence were observed in neonates depending on the type of EtOH exposure received (acute or chronic). These results emphasize the complexity of the disruptive EtOH effects upon breathing at this early and critical stage of development.